Mapping Health Information System For Breast Cancer Patients Through An Epidemiological Study At The Prof.W.Z. Johannes General Hospital And Its Distribution In East Nusa Tenggara Province, Indonesia - Apris Adu (Universitas Nusa Cendana, 2022)
Mapping the spread of disease patients with the Geographic Information System (GIS) is very helpful in providing information on the location of who comes for treatment at the hospital. This research was conducted on all breast cancer patients who were recorded in the medical records of 2017-2019 at Prof. W.Z. Johannes General Hospital Kupang. This research is an analytic observational with a cross-sectional study approach, using a Geographic Information System (GIS) modeling through spatial analysis to obtain an overview of the distribution of breast cancer based on epidemiological variables. Based on the results of research on breast cancer from 2017 to 2019 at Prof. WZ Johannes General Hospital Kupang according to the host epidemiology variable was based on age in highest are between the age of 51 and 60 with 18 patients in total; based on the education level is highest, there are 112 patients in a total of Senior High School graduate; based on the occupation in highest, there are 81 patients worked as Civil Servant, according to the highest time variable in 2019, there were as many as 91 cases, followed by 83 total cases in 2018, and there were as many as 74 cases in 2017.